Cold-Water Corals and Ecosystems 2005
DOI: 10.1007/3-540-27673-4_37
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and nitrogen isotopes of two deep-water corals from the North-East Atlantic: initial results and implications for their nutrition

Abstract: Abstract. The lipid and organic nitrogen isotopic (δ 15 N) compositions of two common deep-water corals (Lophelia pertusa and Madrepora oculata) collected from selected locations of the NE Atlantic are compared to the composition of suspended particulate organic matter, in order to determine their principle food source. Initial results suggest that they may feed primarily on zooplankton. This is based on the increased abundances of mono-unsaturated fatty acids and alcohols and the different ratios of the polyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
95
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 54 publications
10
95
0
Order By: Relevance
“…Indirect diet studies based on δ 15 N trophic status assessments suggest L. pertusa from coral carbonate mounds on Rockall Bank, northeast Atlantic, occupies a similar trophic level to obligate filter-feeding tunicates and bivalve molluscs ). On the other hand, Kiriakoulakis et al (2005) found that L. pertusa from a variety of northeast Atlantic sites were enriched in 2 monounsaturated fatty acids only known to be synthesised by calanoid copepods, implying a more carnivorous diet.…”
Section: Coral Ecophysiologymentioning
confidence: 96%
“…Indirect diet studies based on δ 15 N trophic status assessments suggest L. pertusa from coral carbonate mounds on Rockall Bank, northeast Atlantic, occupies a similar trophic level to obligate filter-feeding tunicates and bivalve molluscs ). On the other hand, Kiriakoulakis et al (2005) found that L. pertusa from a variety of northeast Atlantic sites were enriched in 2 monounsaturated fatty acids only known to be synthesised by calanoid copepods, implying a more carnivorous diet.…”
Section: Coral Ecophysiologymentioning
confidence: 96%
“…There is now evidence for several carbonate mound provinces in the north east Atlantic from (1) south west Ireland: the Hovland (Hovland et al 1994;De Mol et al 2002), Magellan and Belgica provinces (De Mol et al 2002;Van Rooij et al 2003), (2) southern Rockall Bank: Logachev Mounds van Weering et al 2003), (3) western Rockall Bank (Wienberg et al 2008) and (4) generations of coral reef development that leads to coral-built carbonate mounds (Roberts et al 2006). Studies of the stable isotopic composition of coral skeleton and tissue have not supported a seep-based food chain (Duineveld et al 2004) and analyses of lipid biomarkers and stable nitrogen isotopes of Lophelia pertusa and Madrepora oculata point to a diet derived from primary productivity at the surface (Kiriakoulakis et al 2005). Thus to date evidence for a relationship between coral growth and light hydrocarbon seepage has not been found and the mounds are thought to develop through periods of interglacial coral framework growth interspersed with periods of glacial sedimentation over timescales of 1 to 2 million years (Roberts et al 2006;Kano et al 2007).…”
Section: Geological Contextmentioning
confidence: 99%
“…In some situations, the interaction between currents, internal waves, and topography creates suitable conditions for the development of rich benthic communities dominated by suspension-feeding cold-water corals (Genin et al 1986;White et al 2005White et al , 2007. The preferential occurrence of cold-water corals on seafloor relief has been often explained by the topographic acceleration of near-bed currents that enhances food supply (Mortensen et al 2001;Thiem et al 2006;Kiriakoulakis et al 2007). In some locations, internal waves have been found or assumed to play a role in food supply to coldwater coral communities.…”
mentioning
confidence: 99%
“…Cold-water corals were thought to be sustained by local hydrocarbon seepage and chemoautotrophic production (Hovland and Thomsen 1997). Data obtained so far indicate that cold-water coral communities rely on the delivery of phytoplankton, organic matter, and perhaps zooplankton derived from near-surface primary productivity (Duineveld et al 2004(Duineveld et al , 2007Kiriakoulakis et al 2005). Lateral and vertical advection of particles may therefore play an important role in the functioning of coral ecosystems.…”
mentioning
confidence: 99%